Energy Community Surplus Sharing: Solidarity Strategies for Energy Commons Governance - Robert Wade; Francesco Pasimeni; Naud Loomans; Floor Alkemade (International Journal of the Commons)
Energy communities (ECs) have emerged as a new class of ‘prosumers’ in energy transitions. ECs’ ability to sell electricity back to the grid is increasingly curtailed, meaning they are left with decisions on how best to use this common pool of generated electricity. While some ECs can self-consume the generated electricity, a surplus often remains over several timescales. This provides an opportunity for ECs to exchange with actors or households in the local area, but who are not formally involved in the EC. However, most scholarship has assumed a limited subset of prosumer energy exchange possibilities, namely market exchange. Drawing on economic anthropology, this paper explores the possibility of energy sharing between ECs and households beyond market exchange. It explores this using an agent-based model, with agents pursuing their objectives using the levers of sharing, selling and demand flexibility. We find that sharing is the dominant option, even if agents are solely focussed on their own economic benefit. Results also show that integrating local use of electricity and solidarity into agent objectives can improve overall outcomes (highest local use of electricity and improved EC member satisfaction, albeit lower but still slightly positive neighbour household satisfaction). Adjusting market prices (for buying and selling to the grid) can promote efficient surplus energy use, however caution must be given to the distributive implications of this on householders. Finally, this paper reflects on these findings and their wider implications for the governance of energy surplus commons by ECs.